1975
DOI: 10.3109/00498257509052070
|View full text |Cite
|
Sign up to set email alerts
|

Laevo-[1-3H]Methadone Disposition in Tolerant Dogs

Abstract: 1. Following a subcutaneous dose (4mg/kg) of [3H]methadone, peak levels of drug occurred in plasma, tissues and selected areas of the central nervous system (CNS) 2h after injection in both non-tolerant and tolerant dogs. Highest concentrations of methadone were attained in bile and lung compared to other tissues. 2. Levels of methadone in plasma, tissue and CNS of tolerant and non-tolerant animals were not markedly different up to 8h after injection, but a much faster rate of egression of free drug (lower t1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the basis of urinary excretion studies, chlorothiazide appears to be incompletely absorbed from the GI tract of animals and humans (4)(5)(6). These studies reported 1658% urinary recoveries of the oral dose administered to humans.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of urinary excretion studies, chlorothiazide appears to be incompletely absorbed from the GI tract of animals and humans (4)(5)(6). These studies reported 1658% urinary recoveries of the oral dose administered to humans.…”
Section: Resultsmentioning
confidence: 99%
“…8 By bridging the two phenyl rings found in the azauracil substituent of 3 and 4, one may produce a variety of tricyclic azauracil substituents which could in theory exhibit all of the substituent properties detailed above. A feature common to the aryl moiety of 2-4 is the presence of a meta substituent.…”
Section: Methodsmentioning
confidence: 99%